Classroom acoustics for acceptable speech recognition: A review - Bradley, J.S. (Canadian Acoustics, 2002)
The basic acoustical requirements for accpetable speech recognition in classrooms were investigated. The scores for speech intelligibility increased with increasing signal-to-noise ratio until near 100% intelligibility was reached. The study was useful in determining safe teacher voice levels and the required speech/noise ratio for all ages of children.